Rhombic Dodecahedron ZIF‐8 Precursor: Designing Porous N‐Doped Carbon for Sodium‐Ion Batteries. Issue 12 (14th September 2017) - Liu, Yang; Wei, Gangya; Pan, Liudi; Xiong, Mingyan; Yan, Honglin; Li, Yuxi; Lu, Cong; Qiao, Yun
Abstract: The design and synthetic strategy of nanostructure electrodes are crucial in the rapid development of sodium‐ion batteries for energy storage device. Rhombic dodecahedral N‐doped carbon with a porous structure has been prepared by using ZIF‐8 as the precursor, which could be beneficial for electrolyte permeation as well as electron and ion transportation. The nitrogen content and surface structure can be adjusted by controlling the heating temperature. As an anode for sodium‐ion batteries, the as‐derived porous N‐doped carbon with a rhombic dodecahedral structure demonstrates a very high reversible capacity above 300 mA h g −1 after 500 cycles at a current density of 0.5 A g −1, as well as a good cycle stability and excellent rate capability, which could make it an excellent candidate for sodium‐ion batteries with high performance. Additionally, the as‐assembled full cell, using Prussian blue as the cathode, displays a capacity of 76 mA h g −1 at 0.1 A g −1 after 50 cycles. In this way, this work will expand the application of metal‐organic frameworks and their derivatives in large‐scale electric energy storage. Abstract : Off the grid : Rhombic dodecahedral N‐doped carbon with a porous structure is obtained by using ZIF‐8. A Prussian blue//ZIF‐derived carbon sodium‐ion full battery is built, which demonstrates a stable discharge capacity of 76 mA h g −1 after 50 cycles at a current density of 0.1 A g −1 . ZIF could be a promising and outstanding candidate to design functional carbon for sodium‐ion batteries in grid storage.